The Need for Mandatory Autopsy Teaching in Forensic Medicine for Medical Students - Nurul Kharmila Abdullah; Nur Arina Ahmad; Shalinawati Binti Ramli; Nadiawati Abdul Razak (Hospital Universitário of the Universidade de São Paulo (HU USP), 2024)
Indexed by Scopus